Influence of tourist-to-tourist interaction and environmental contextual factors on tourists’ pro-environmental behaviors in China - Xiao, Yue (2022)
Tourists’ illegal behaviors are one of the main reasons for the environmental problems of China’s tourism industry. In recent years, more tourism researchers began to pay attention to the role of tourists and their actions in the ecological protection of tourist destinations, namely tourists' pro-environmental behaviors. However, previous researches on pro-environmental behaviors usually focused on tourists’ individual factors but ignored the impact of contextual interaction factors. Therefore, this thesis tries to fill in the literature gap by exploring the influence of tourist-to-tourist interaction and environmental contextual factors on tourists’ pro-environmental behaviors (PEB). Taking three important theories such as norm activation model (NAM), social capital theory, and broken window theory as the theoretical basis, this study explains tourists’ pro-environmental behaviors from interpersonally and environmentally contextual perspectives. It selects interpersonal ties, group norms, and social trust of tourist interaction and environmental contextual factors as external factors to study their influences on the internal factors of tourists’ proenvironmental behaviors. And face-to-face questionnaires are used to collect dates and Partial least squares (PLS), which is a variance-based SEM method to evaluate hypotheses. As a result, the findings of this study revealed that 1) Group norms, personal norms, social trust and environmental contextual factors have a direct impact on the pro-environmental behavior; 2) Ascription of responsibility and group norms have an indirect impact on the pro-environmental behavior via personal norms; 3) while awareness of consequences has an indirect impact on personal norms via ascription of responsibility; 4) interpersonal ties regulate the relationship between group norms and pro-environmental behaviors. This study has added value to the social capital theory, broken window theory, and the NAM in their applicability’s in explaining tourists’ PEB. Plus, it provided a feasible interaction direction for Chinese tourism managers to guide tourists' PEB.